The new curriculum and teacher performance. - Morgan, Nicolette Genevive (2008)
M.Ed. === This research dissertation sought to discover how teachers have interacted with the New Curriculum, it is, the newly designed Curriculum 2005 (C2005) and the subsequent Revised New Curriculum Statement that featured in the educational realm in South Africa in recent years. It was an attempt at discovering both the mental and physical attributes that teachers conveyed whilst implementing the Curriculum. The qualitative research approach was used in the study, which allowed for an in-depth insight into the day to day successes or failures that both teachers and learners experienced in the classroom. With the use of the interview guide, responses that surfaced, gave the researcher the opportunity to divulge further into the weaknesses or strengths that the New Curriculum possesses. The researcher discovered through this study that there were many controversial issues that surrounded the implementation of the New Curriculum. Thus, the focus remained on the how the most important stakeholders, the teachers, expressed their views pertaining to the Curriculum. The study provided evidence that suggests that teachers need to and should be included in all curriculum planning processes. === Dr. M.C. van Loggerenberg